2005
DOI: 10.1128/mcb.25.17.7449-7458.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pam17 Is Required for Architecture and Translocation Activity of the Mitochondrial Protein Import Motor

Abstract: Import of mitochondrial matrix proteins involves the general translocase of the outer membrane and the presequence translocase of the inner membrane. The presequence translocase-associated motor (PAM) drives the completion of preprotein translocation into the matrix. Five subunits of PAM are known: the preproteinbinding matrix heat shock protein 70 (mtHsp70), the nucleotide exchange factor Mge1, Tim44 that directs mtHsp70 to the inner membrane, and the membrane-bound complex of Pam16-Pam18 that regulates the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 50 publications
7
111
1
1
Order By: Relevance
“…mtHsp70 is recruited to the translocase by Tim44 and binds to the incoming precursors in an ATP-dependent manner that is regulated by nucleotide exchange factor Mge1 and the J-complex Tim14-Tim16. In addition to these eight subunits essential for cell viability and function of the translocase, the TIM23 complex contains two recently identified nonessential subunits, Tim21 and Pam17 Mokranjac et al, 2005;van der Laan et al, 2005), which appear to modulate the activity of the translocase in an antagonistic manner .…”
Section: Introductionmentioning
confidence: 99%
“…mtHsp70 is recruited to the translocase by Tim44 and binds to the incoming precursors in an ATP-dependent manner that is regulated by nucleotide exchange factor Mge1 and the J-complex Tim14-Tim16. In addition to these eight subunits essential for cell viability and function of the translocase, the TIM23 complex contains two recently identified nonessential subunits, Tim21 and Pam17 Mokranjac et al, 2005;van der Laan et al, 2005), which appear to modulate the activity of the translocase in an antagonistic manner .…”
Section: Introductionmentioning
confidence: 99%
“…Pam18 inactivation after precursor accumulation led to a similar loss of the TOM/TIM23 supercomplex, as observed in the ssc1-3 mutant. Although previous BN-PAGE analyses indicated that mtHsp70/Tim44 were not a stoichiometric constituents of the TOM/TIM23 supercomplex 25 , subsequent analyses showed that all constituents of the import motor are recovered with the TOM/ TIM23 supercomplex when mild affinity isolations are employed 13,[26][27][28][29][30] . Accordingly, at the active translocase, ATP hydrolysis by Hsp70, stimulated by its co-chaperone Pam18, was required to sustain the matrix-destined translocation intermediate.…”
Section: Import Motor Activity Maintains a Tom/tim23 Intermediatementioning
confidence: 99%
“…In contrast to mutants of the co-chaperones, pam17D and mgr2D cells are viable, but are characterized by growth retardation 28,32 . Nevertheless, pam17D and mgr2D mitochondria displayed selective matrix protein import defects (Fig.…”
Section: Import Motor Activity Maintains a Tom/tim23 Intermediatementioning
confidence: 99%
See 1 more Smart Citation
“…The PAM complex, consisting of Pam16p, Pam17p, Pam18p, mtHsp70, Mge1p and Tim44p, modulates the translocation of proteins into the matrix [4,28,35,36]. Therefore, impaired PAM machinery function leads to defects in the import of matrix-targeted proteins [28].…”
Section: The Pam Complex Mediates the Import Of Tm3-6 Of Mdl1pmentioning
confidence: 99%